Memahami Strategi Financial Management Bagi Siswa SMK Bina Patriot - Ririn Uke Saraswati; Sri Winda Hardiyanti Damanik; Soedjatmoko Soedjatmoko; Arrofie Darmawan; Sony Sonjaya; Fenika Bunga Prawida Suwanto; Khairil Anwar; Sandi Arif Setiadi; Winda Neri Sari (Nusantara Mengabdi Kepada Negeri, 2024)
Financial management is a field of management related to planning, examining, controlling, managing and storing activities carried out by individuals, organizations or companies. The importance of understanding financial management strategies well is not only for workers who already have income, but also for students who will one day enter the workforce and will have their own income. Community service activities with the theme "Financial Management Strategies for Students" carried out at SMK Bina Patriot located in Bekasi were carried out through a seminar method by presenting speakers from lecturers and students. This activity was attended by class XII participants as many as 45 participants. With this seminar, it is hoped that students can understand the importance of planning, managing, and investing their money wisely so as to avoid financial problems in the future. Based on the results of a survey conducted as feedback on this activity, it can be seen that 64.3% of participants stated that this seminar was very useful